Effects of hydrocolloid addition and high pressure processing on the rheological properties and microstructure of a commercial ostrich meat product "Yor" (Thai sausage) - Utaiwan Chattong (2018)
"Yor" is a traditional sausage like product widely consumed in Thailand. Its textures are usually set by steaming, in this experiment ultra-high pressure was used to modify the product. Three types of hydrocolloid; carboxymethylcellulose (CMC), locust bean gum (LBG) and xanthan gum, were added to minced ostrich meat batter at concentration of 0-1% and subjected to high pressure 600 MPa, 50 °C, 40 min. The treated samples were analysed for storage (G′) and loss (G″) moduli by dynamic oscillatory testing as well as creep compliance for control stress measurement. Their microstructures using confocal microscopy were also examined. Hydrocolloid addition caused a significant (P < 0.05) decrease in both the G′ and G″ moduli. However the loss tangent of all samples remained unchanged. Addition of hydrocolloids led to decreases in the gel network formation but appears to function as surfactant materials during the initial mixing stage as shown by the microstructure. Confocal microscopy suggested that the size of the fat droplets decreased with gum addition. The fat droplets were smallest on the addition of xanthan gum and increased in the order CMC, LBG and no added gum, respectively. Creep parameters of ostrich yors with four levels of xanthan gum addition (0.50%, 0.75%, 1.00% and 1.25%) showed an increase in the instantaneous compliance (J0), the retarded compliance (J1) and retardation time (λ1) but a decrease in the viscosity (η0) with increasing levels of addition. The results also suggested that the larger deformations used during creep testing might be more helpful in assessing the mechanical properties of the product than the small deformations used in oscillatory rheology. © 2007 Elsevier Ltd. All rights reserved.